CHILD TRAFFICKING AND CITIZEN SECURITY. CASE METROPOLITAN LIMA, 2016 - Garro Vasquez, Odalis Juana (2021)
Peruvian legislation, in accordance with international standards, establishes that the recruitment, transportation, transfer, harboring, reception or retention of children or adolescents for the purpose of exploitation of any kind is considered trafficking in persons. Consequently, this activity will be punished with imprisonment, according to the magnitude of the crime. Therefore, the general objective of the study was to determine the relationship between trafficking in minors and citizen security in Metropolitan Lima, 2016”. The method employed in the study is descriptive correlational. It is descriptive in terms of its methodological scope because it aims to know precisely the magnitude of a situation, hierarchize the problems, identify its variables and point out the guidelines for hypothesis testing. And it is correlational because it relates child trafficking with citizen security. The most important result is presented in the general conclusion, which revolved around the main modalities of child trafficking, related to citizen security, are: sexual exploitation of minors, illicit drug trafficking and forced child labor.